Is Adult Tetanus an Endemic in India? - Surabhi GS; Prithviraj, Renuka; Lavanya R (National Journal of Community Medicine, 2022)
Background: Tetanus is a life-threatening disease in developing country like India, with high morbidity and mortality rate. Though maternal and neonatal tetanus is eliminated, adult tetanus still remains in boom and is overlooked. Methods: An observational descriptive study using retrospective secondary data was undertaken among the patients admitted to a regional referral hospital to study the epidemiological factors influencing tetanus, clinical features and the outcome of tetanus. Results: Analysis of 41 clinically diagnosed cases of tetanus showed that, majority were in 50-69 years of age group who resided in rural area and agriculture was their main occupation. Case fatality rate was 53.6% which revealed that mortality was the major outcome. And 95% of those infected were not aware of their immunization status. Conclusion: An early diagnosis, a proper wound management immediately after the injury, health education programs to create awareness among the public not to neglect even trivial injuries would definitely lead India to the path of elimination of adult tetanus. Strong emphasis is to be laid on adult immunization beyond the age of 10 years.